The Economic Crisis and Regulation - Potocskáné Kőrösi, Anita; Bertalan, Péter (Acta Scientiarum Socialium, 2015)
The Economic Crisis and Regulation. The economic and financial crisis that spread from the US had deeply struck the whole world including the Central and Eastern European region. For a long time there was no adequate answer to solve the problems, only confusion. Not only the long term strategy, but also the agreement concerning the urging, immediately necessary actions was missing. European governments have rec-ognised the need of taking strong measures but it is a question whether they used the proper methods and were they sufficient and effective enough to treat the situation. To get through the crisis the consolidation of the banking system, restoration of liquidity and increase of bank lending were needed so an extensive reform of insti-tutional structure of financial regulation and banking system was inevitable. It became clear that the recession can be managed only if besides the stabilization of banks, they reconsider the whole financial regulation. The measures taken by the governments and special elements of the actions are highly controversial, so there is no consensus about whether these reforms will remain appropriate and sufficient in the future even in case of another forthcoming crisis. On the whole it’s obvious that the global financial and economic crisis caused serious problems in employment, real economy and in social life of the countries and consequently affected their political system and power relations.